(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
The decree of the President of the Republic of Uzbekistan "On approval of the concept of development of the higher education system of the Republic of Uzbekistan until 2030" on the basis of international experience provides for the introduction of advanced standards of higher education, including a gradual transition from education aimed at obtaining theoretical knowledge to educational programs to an education system aimed at; such tasks as raising the content of higher education to a qualitatively new level, creating a system of training highly qualified personnel who will make a worthy contribution to the sustainable development of the social sphere and economic sectors, will be able to find a place in the labor market [1].